O currículo oculto no ensino de ciências: uma análise crítica da Base Nacional Comum Curricular - Bimbatti, Bianca Rita (Universidade Federal de São Carlos, 2021)
Historically, school has been used as an important space for social control and maintenance of classes, relying on the curriculum as an important tool for the production and reproduction of values, behaviors and meanings aligned with the interests of the capitalist social and economic organization model. With the neoliberal politics’ advancement, a National Curriculum Common Core (BNCC) is being imposed on schools as an important element for the development of a more just, democratic and quality education. However, the BNCC reveals itself as another instrument in service of the capitalist financial market. In this work, the BNCC was analyzed from a critical perspective, in order to highlight the presence of the hidden curriculum in the proposals of the BNCC for the Natural Sciences’ area, and to understand how such hidden curricular practices contribute to the maintenance of the current productive system. From a documental analysis guided by the qualitative research method, Paulo Freire's pedagogical and epistemological contributions to overcome the hidden curriculum were used for the development of this work, using three parameters: historical-dialectical materialism, dialogue and concrete reality. Throughout this work, it was possible to highlight the role of BNCC in legitimizing an instrumental and decontextualized science teaching, contributing to the normalization of social contradictions and adaptation of the students to the current reality.
The hidden curriculum in science education: a critical analysis of the National Curriculum Common Core
Keywords: Currículo oculto; BNCC; Ensino de ciências; Hidden curriculum; BNCC; Science teaching; CIENCIAS HUMANAS::EDUCACAO::CURRICULO